The cell-permeant antioxidant D-thiol ester D-cysteine ethyl ester overcomes physical dependence to morphine in male Sprague Dawley rats - Getsy, Paulina M.; Coffee, Gregory A.; Bates, James N.; Parran, Theodore; Hoffer, Lee; Baby, Santhosh M.; MacFarlane, Peter M.; Knauss, Zackery T.; Damron, Derek S.; Hsieh, Yee-Hsee; Bubier, Jason A.; Mueller, Devin; et al. (Frontiers in Pharmacology, 2024)
The ability of morphine to decrease cysteine transport into neurons by inhibition of excitatory amino acid transporter 3 (EAA3) may be a key molecular mechanism underlying the acquisition of physical and psychological dependence to morphine. This study examined whether co-administration of the cell-penetrant antioxidant D-thiol ester, D-cysteine ethyl ester (D-CYSee), with morphine, would diminish the development of physical dependence to morphine in male Sprague Dawley rats. Systemic administration of the opioid receptor antagonist, naloxone (NLX), elicited pronounced withdrawal signs (e.g., wet-dog shakes, jumps, rears, circling) in rats that received a subcutaneous depot of morphine (150 mg/kg, SC) for 36h and continuous intravenous infusion of vehicle (20 L/h, IV). The NLX-precipitated withdrawal signs were reduced in rats that received an infusion of D-CYSee, but not D-cysteine, (both at 20.8 mol/kg/h, IV) for the full 36h. NLX elicited pronounced withdrawal signs in rats treated for 48h with morphine (150 mg/kg, SC), plus continuous infusion of vehicle (20 L/h, IV) that began at the 36h timepoint of morphine treatment. The NLX-precipitated withdrawal signs were reduced in rats that received a 12h infusion of D-CYSee, but not D-cysteine, (both at 20.8 mol/kg/h, IV) that began at the 36h timepoint of morphine treatment. These findings suggest that D-CYSee may attenuate the development of physical dependence to morphine and reverses established dependence to the opioid in male Sprague Dawley rats. Alternatively, D-CYSee may simply suppress the processes responsible for NLX-precipitated withdrawal. Nonetheless, D-CYSee and analogues may be novel therapeutics for the treatment of opioid use disorders.